Imago Dei and artificial intelligence: A theological inquiry into personhood and human ontological boundaries - Hermanto, Yanto P. (Hervormde teologiese studies, 2025)
Advancements in artificial intelligence (AI) technology challenge traditional theological understandings of human personhood. This article examines the concept of personhood in light of the doctrines of Imago Dei, Christology and pneumatology, and contrasts it with the phenomenon of ‘simulated personhood’ in AI. Employing a systematic theological approach and interdisciplinary reflection, the article argues that human personhood is rooted in Trinitarian relationality and participation in the Holy Spirit – dimensions that cannot be reduced to cognitive functions or digital simulations. Contribution: The original contribution of this study lies in introducing the category of ‘simulated personhood’ and in developing a framework for digital pastoral theology. Engagement with African theological voices enriches the analysis of personhood as a relational and communal reality. The article concludes with recommendations for further research in the areas of digital liturgy, contextual pneumatology and the ethics of technology.